PENGARUH KEPRIBADIAN DAN PENGALAMAN TERHADAP EFEKTIFITAS MANAJERIAL KEPALA SEKOLAH SMP NEGERI DI WILAYAH JAKARTA TIMUR - Serepina Tiurmaida (Jurnal Manajemen Pendidikan, 2013)
The objective of this research is to study information about the effect of personality and experience on the managerial effectiveness. The research was conducted to all of State Junior High Schools Principals in The City of East Jakarta by using a survey method with path analysis applied in testing hypothesis. The sample size in the research was done to 77 principals with samples taken using simple random sampling. The result shows that there are direct influence of the followings: (1) there is positively direct effect of personality on the managerial effectiveness. (2). there is positively direct effect of experience on the managerial effectiveness. (3) there is positively direct effect of personality on the experience. It is expected that the results of the research could be implied in increasing and optimalizing the managerial effectiveness, personality and experience should be taken into account.